142k views
2 votes
Expanding Logarithmic Expressions In Exercise, use the properties of logarithms to rewrite the expression as the sum, difference, or multiple of logarithms.

In(x - 1/x + 1)^2

User Cyberflohr
by
6.0k points

2 Answers

3 votes

We can use two properties to solve:

Quotient Rule:
\text{ln}(x)/(y) = \text{ln}(x)-\text{ln}(y)

Power Rule:
\text{ln}(x)^p = p~\text{ln}(x)

Simplify the expression using the power rule:

In(x - 1/x + 1)^2 → 2 ln (x - 1/x + 1)

Simplify using the quotient rule:

2 ln (x - 1/x + 1) → 2[ln(x - 1) - ln(x + 1)]

Therefore, the the simplified logarithm is 2[ln(x - 1) - ln(x + 1)]

Best of Luck!

User Curlene
by
6.4k points
6 votes

Answer:
2[\ln(x-1)-\ln(x+1)]

Explanation:

We know that , the properties of logarithm are:

P[1]
\log (ab)= \log a+\log b

P[2]
\log((a)/(b))=\log a-\log b

P[3]
\log a^n= n\log a

The given expression in terms of Natural log :
\ln ((x-1)/(x+1))^(2)


=2\ln (((x-1)/(x+1)) [ By using P[3]]


=2[\ln(x-1)-\ln(x+1)] [ By using Property (1)]

Hence, the simplified expression becomes
2[\ln(x-1)-\ln(x+1)] .

User Zenpoy
by
6.1k points